(Re)Shaping History in Bosnian and Herzegovinian Museums - Lozic, Vanja (Culture Unbound, 2015)
The current article explores how political changes in the past 130 years have shaped and reshaped three major museums in Bosnia and Herzegovina (BiH). The overall aim is to describe structural processes of national museum building in BiH and the ways the museological representation of history is connected to state and nation making and to political transitions and crises. The analysed museums are the National Museum of BiH, the History Museum of BiH, and the Museum of the Republic of Srpska. The source material analysed consists of the directories and the titles of exhibitions; secondary material, which describes previous exhibitions; and virtual museum tours. The article illustrates that during the Austrian-Hungarian Empire, which established the National Museum in 1888, the museum played an important part in the representation of Bosnian identity (bosnjastvo). After World War II, in the Socialist Federal Republic of Yugoslavia, all three analysed museums were summoned to interpret the past in accordance with the guidelines of the communist regime. Since the 1990s, a highly ethnicized process of identity building and of the musealization of heritage, and history permeates all three museums analysed here. When it comes to the central exhibition-themes following the 1990s war, one could conclude that whereas the National Museum and the History Museum highlight the recent creation of an independent BiH and ostracize BIH-Serbs, the Museum of the Republic of Srpska asserts the ostensible distinctiveness of the Republic of Srpska and excludes the narratives about BiH as a unified and independent nation-state. If an agreement about the future of BiH and its history is to be reached, a step towards multi-vocal historical narratives has to be made from both sides.